Swimming and respiratory muscle endurance training: A case study - Lemaitre, F.; Chavallard, F.; Chollet, D. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of this case study was to investigate whether respiratory muscle endurance training (RMET) would increase performance in a long-distance swimmer. An expert long-distance swimmer trained for 10 weeks in a RMET program (30 minutes a day, 5 days a week) plus his usual swim training. Maximal swim time trials, ventilatory function tests, maximal inspiratory and expiratory pressure (MIP and MEP), and respiratory endurance tests (RET) were done. Ventilatory function parameters were not improved post-training, but MIP, MEP, RET and swimming performance were increased (+19%, +33%, +7 minutes; 50 m: -5.4%; 200 m: -7.2% respectively). RMET may be thus a useful technique to improve performance in long-distance swimmers.